Reprogramming the tumor metastasis cascade by targeting galectin-driven networks - Perrotta, Ramiro Martin (2021)
A sequence of interconnected events known as the metastatic cascade promotes tumor progression by regulating cellular and molecular interactions between tumor, stromal, endothelial, and immune cells both locally and systemically. Recently, a new concept has emerged to better describe this process by defining four attributes that metastatic cells should undergo. Every individual hallmark represents a unique trait of a metastatic cell that impacts directly in the outcome of the metastasis process. These critical features, known as the hallmarks of metastasis, include motility and invasion, modulation of the microenvironment, cell plasticity and colonization. They are hierarchically regulated at different levels by several factors, including galectins, a highly conserved family of β-galactoside-binding proteins abundantly expressed in tumor microenvironments and sites of metastasis. In this review, we discuss the role of galectins in modulating each hallmark of metastasis, highlighting novel therapeutic opportunities for treating the metastatic disease.